PENGARUH KUALITAS PRODUK DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING: STUDI PADA PENGGUNA PRODUK SKINCARE MS GLOW DI KABUPATEN PATI - Ambarwati, Putri; Prabowo, Heri; Widiastuti, C. Tri (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to determine the effect of product quality, social media marketing on decisions with purchase intention as an intervening variable in users of MS Glow skincare products in Pati Regency. The population used is all users of MS Glow skincare products in Pati Regency. This study uses non-probability sampling techniques, namely purposive sampling where the sample is taken based on certain criteria that must be met and the sample used is 97 respondents. This study uses the Partial Least Square-Structural Equation Modeling (PLS-SEM) method, which is run with the help of SmartPLS version 3.0 software. to analyze the data. Based on the results of the study, it shows that the variables of product quality and social media marketing have no significant effect on purchasing decisions. Product quality and social media marketing variables have a positive and significant effect on purchase intention. The purchase interest variable has a positive and significant effect on purchasing decisions. Purchasing interest variables can mediate the effect of product quality on purchasing decisions. The purchase interest variable cannot mediate the effect of social media marketing on purchasing decisions